Accessibility Compliance: One State, Two Approaches. Issue 1 (31st May 2018) - Adams, Stephanie J.; Halaychik, Corey; Mezick, Jennifer
ABSTRACT: As a result of a 2014 recommendation from the Tennessee Higher Education Commission, the Tennessee Board of Regents (TBR) and University of Tennessee (UT) Systems were required to develop policies ensuring that the systems' colleges and universities provide students with accessible information materials, including library e-resources. The two systems have chosen to approach accessibility compliance in different ways. The TBR System formed the TBR Libraries Accessibility Task Force, whose members have created a process for collecting accessibility compliance documentation from vendors and are currently developing a procedure for auditing library e-resources. The UT System has focused on developing licensing language for e-resources that addresses accessibility compliance. This conference report details the two systems' approaches and provides an overview of accessibility and accessible design features, laws and complaints related to inaccessible materials in libraries and higher education, and accessibility document standards.